Implementasi E-Form dalam Pelaporan SPT Tahunan Orang Pribadi Sebagai Wujud Kepatuhan Pajak pada KKP ABC (Jurnal Riset Manajemen dan Akuntansi, 2025)
This research discusses the effectiveness of E-Form implementation in increasing the level of tax compliance of Individual Taxpayers served by the ABC CTF. This research uses a descriptive qualitative approach with a case study method, where data is collected through direct observation activities in the field as well as documentation during the tax reporting process using E-Form. The results indicate that the E-Form provides ease of access, time efficiency, and flexibility in reporting, thereby contributing positively to formal taxpayer compliance, particularly in terms of timeliness and completeness of documentation. However, challenges remain regarding digital literacy and technical understanding. Support from tax consultants has proven helpful in overcoming these obstacles. Therefore, the E-Form is considered effective as a digital innovation in strengthening a culture of tax compliance, although continued efforts in education and outreach are still necessary.